71 'Game changers' decoding media misrepresentation of medical evidence. (8th June 2022) - Perry, Danielle; Thomas, Betsy; Kirkwood, Jessica
Abstract : In a world of unlimited information, it feels like everyone believes they can be an expert on medical interventions, including our patients. How do we help inform our patients of the true benefits and harms of medical treatments? In this presentation, we will highlight some of the ways media distorts effect estimates and how we should be interpreting them, based on the medical literature. Finally, we will explore ways to communicate risk with your patients, including using icon arrays or other clinical decision tools. Objectives: At the conclusion of this activity, in regard to evidence-based benefit and harms, participants will be able to: Describe how they are portrayed by the media. Interpret the various types of effect estimates in medical literature. Discuss how benefits and harms can be incorporated into shared informed decision making, using clinical examples.